2023
DOI: 10.1101/2023.08.07.552303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitory subpopulations in preBötzinger Complex play distinct roles in modulating inspiratory rhythm and pattern

Abstract: Inhibitory neurons embedded within mammalian neural circuits shape breathing, walking, chewing, and other rhythmic motor behaviors. At the core of the neural circuit controlling breathing is the preBötzinger Complex (preBötC), a nucleus in the ventrolateral medulla necessary for generation of inspiratory rhythm. In the preBötC, a recurrently connected network of glutamatergic Dbx1-derived (Dbx1+) neurons generates rhythmic inspiratory drive to inspiratory premotoneurons and motoneurons. Functionally and anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Consistently, transcriptomic analysis has revealed that the expression profiles of various neurexins differ remarkably in excitatory neurons versus inhibitory neurons even among distinct subtypes of interneurons (Foldy et al, 2016 ;Fuccillo et al, 2015 ;Lukacsovich et al, 2019 ;Uchigashima et al, 2019 ). Despite the multifaceted roles of neurexins widely observed in various glutamatergic and GABAergic synapses (Boxer and Aoto, 2022 ;Chen et al, 2017 ;Luo et al, 2021 ;Sudhof, 2017 ), however, it remains largely unknown how neurexins may regulate the functional properties of the glycinergic synapses, which mediate essential inhibition in the spinal cord, brainstem and retina (Assareh et al, 2023 ;Brill et al, 2020 ;Chang et al, 2023 ;Feng et al, 1998 ;Foster et al, 2015 ;Gomeza et al, 2003a ;Gomeza et al, 2003b ;Zeilhofer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 98%
“…Consistently, transcriptomic analysis has revealed that the expression profiles of various neurexins differ remarkably in excitatory neurons versus inhibitory neurons even among distinct subtypes of interneurons (Foldy et al, 2016 ;Fuccillo et al, 2015 ;Lukacsovich et al, 2019 ;Uchigashima et al, 2019 ). Despite the multifaceted roles of neurexins widely observed in various glutamatergic and GABAergic synapses (Boxer and Aoto, 2022 ;Chen et al, 2017 ;Luo et al, 2021 ;Sudhof, 2017 ), however, it remains largely unknown how neurexins may regulate the functional properties of the glycinergic synapses, which mediate essential inhibition in the spinal cord, brainstem and retina (Assareh et al, 2023 ;Brill et al, 2020 ;Chang et al, 2023 ;Feng et al, 1998 ;Foster et al, 2015 ;Gomeza et al, 2003a ;Gomeza et al, 2003b ;Zeilhofer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 98%
“…Consistently, transcriptomic analysis has revealed that the expression profiles of various neurexins differ remarkably in excitatory neurons versus inhibitory neurons even among distinct subtypes of interneurons ( Földy et al, 2016 ; Fuccillo et al, 2015 ; Lukacsovich et al, 2019 ; Uchigashima et al, 2019 ). Despite the multifaceted roles of neurexins widely observed in various glutamatergic and GABAergic synapses ( Boxer and Aoto, 2022 ; Chen et al, 2017 ; Luo et al, 2021 ; Südhof, 2017 ), however, it remains largely unknown how neurexins may regulate the functional properties of the glycinergic synapses, which mediate essential inhibition in the spinal cord, brainstem and retina ( Assareh et al, 2023 ; Brill et al, 2020 ; Chang et al, 2023 ; Feng et al, 1998 ; Foster et al, 2015 ; Gomeza et al, 2003a ; Gomeza et al, 2003b ; Zeilhofer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, transcriptomic analysis has revealed that the expression profiles of various neurexins differ remarkably in excitatory neurons versus inhibitory neurons even among distinct subtypes of interneurons (Foldy et al, 2016; Fuccillo et al, 2015; Lukacsovich et al, 2019; Uchigashima et al, 2019). Despite the multifaceted roles of neurexins widely observed in various glutamatergic and GABAergic synapses (Boxer and Aoto, 2022; Chen et al ., 2017; Luo et al, 2021; Sudhof, 2017), however, it remains largely unknown how neurexins may regulate the functional properties of the glycinergic synapses, which mediate essential inhibition in the spinal cord, brainstem and retina (Assareh et al, 2023; Brill et al, 2020; Chang et al, 2023; Feng et al, 1998; Foster et al, 2015; Gomeza et al, 2003a; Gomeza et al, 2003b; Zeilhofer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%